Plant biodiversity : monitoring, assessment and conservation - Ansari, Abid A. Sarvajeet Singh Gill Zahid Khorshid Abbas M Naeem (CAB International, 2017)
This book contains 30 chapters focusing on the importance of plant biodiversity monitoring and assessment to help prevent species extinction, ecosystem collapse and solve problems in biodiversity conservation.